Temporal and spatial transferability in telemetry-based dynamic species distribution models: The effects of algorithms and pseudo-absence techniques - Joshua C Wilson; Philip N Trathan; Hugh J Venables; Horst Bornemann; Rochelle Constantine; Daniel P Costa; Luciano Dalla Rosa; Louise Emmerson; Ari S Friedlaender; Michael E Goebel; Simon Goldsworthy; Mark A Hindell; et al. (Ecological Modelling, 2026)

Estrus monitoring in giant pandas revisited: The importance of assay selection - Tom Cools; Kirsten S. Wilson; Catherine Vancsok; Baptiste Mulot; Antoine Leclerc; Marko Haapakoski; José Kok; W. Colin Duncan; Simon Girling; Yingmin Zhou; Rengui Li; Desheng Li; et al. (Animal Reproduction Science, 2026)

Reconstructing one of the largest explosive eruptions of the Quaternary through high-resolution tephra geochemistry: the 349 ka Whakamaru supereruption - Anna L. Miller; Simon J. Barker; Colin J.N. Wilson (Journal of Volcanology and Geothermal Research, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Origins and environmental impacts of distal rhyolitic tephra layers on Chatham Island, New Zealand - Anna L. Miller; Simon J. Barker; Katherine A. Holt; Stephen B. Piva; Colin J. N. Wilson (Journal of Quaternary Science, 2026)
Chatham Island, ~700 km east of mainland New Zealand, preserves several macroscopic tephra beds, sourced from the central Taupō Volcanic Zone (TVZ) some 850 km away. These layers, often enclosed within peat, provide insights into the eruptive characteristics, timing and paleoenvironmental impacts of large explosive rhyolitic eruptions in a distal setting. We report the nature, origins and impacts of these tephras by documenting bulk and centimetric‐scale stratigraphic changes in glass shard geochemistry and millimetric‐scale changes in pollen assemblages in the enclosing peats. Three layers are investigated: the ~25.5 ka Kawakawa–Ōruanui Tephra (KOT), the ~345 ka Rangitawa Tephra and one newly discovered tephra. The KOT shows no stratigraphic variability in glass composition throughout ~15 cm thickness. The Rangitawa Tephra contains three glass populations that were deposited sequentially throughout the eruption and further link this tephra to the Whakamaru supereruption. The new tephra has two glass populations and is matched to the ~322 ka Matahina caldera‐forming eruption. High‐resolution sampling of peat bracketing the KOT and Rangitawa Tephra reveals marked changes in local vegetation following the deposition of both tephras. The nature of the changes varies between events and can be explained by differing paleoenvironmental settings, climate and/or tephra thickness.

Neodymium isotopes in marginal seawater trace continental weathering inputs - Zhaojie Yu; Zehua Song; Xiaojie Tang; David J. Wilson; Germain Bayon; Yi Huang; Xiaoying Kang; Hualong Jin; Shiming Wan; Christophe Colin (Geochimica et Cosmochimica Acta, 2026)

Large-scale rift-related faulting linked to a caldera-forming eruption: A case study from Taupō, New Zealand - Alex S. Gold; Madisen Snowden; James D. Muirhead; Pilar Villamor; Genevieve L. Coffey; Colin J.N. Wilson; Regine Morgenstern (Journal of Volcanology and Geothermal Research, 2026)

Recycling of ash particles during highly explosive eruptions: multiple glass populations in the 1.8 ka Taupō tephra - Simon J. Barker; Stephen B. Piva; Colin J. N. Wilson; David J. Lowe; Bruce L. A. Charlier; Alan R. Orpin (Bulletin of Volcanology, 2025)

Arsenic speciation and mobility in gold mining-impacted riverine sediments from the Loddon River catchment in Victoria, Australia - Francesco Colombi; Ewen Silvester; Aleicia Holland; Darren Baldwin; Colin MacRae; Nick Wilson; Ian Rutherfurd; James Grove; Jodi Turnbull; Mark Macklin; Peter Davies; Susan Lawrence (Applied Geochemistry, 2025)

Predicting wave runup on composite beaches - Matthew P. Conlin; Gregory Wilson; Hailey Bond; Dorukhan Ardağ; Colin Arnowil (Coastal Engineering, 2025)

An investigation of an outbreak of Salmonella Typhimurium infections linked to cantaloupe – United States, 2022 - Sharon Seelman Federman; Erin Jenkins; Cullen Wilson; Arturo DeLaGarza; Colin Schwensohn; Benjamin Schneider; Johnson Nsubuga; Robert Literman; Allison Wellman; Brooke M. Whitney; Rebecca L. Bell; Kerri Harris-Garner; et al. (Food Control, 2024)

The Visual Monitoring Camera (VMC) on Mars Express: A new science instrument made from an old webcam orbiting Mars - Jorge Hernández-Bernal; Alejandro Cardesín-Moinelo; Ricardo Hueso; Eleni Ravanis; Abel Burgos-Sierra; Simon Wood; Marc Costa-Sitja; Alfredo Escalante; Emmanuel Grotheer; Julia Marín-Yaseli de la Parra; Donald Merrit; Miguel Almeida; et al. (Planetary and Space Science, 2024)

Impact of riverine sediment mineralogy on seawater Nd isotope compositions in the northeastern part of the Indian Ocean during the last two glacial cycles - Yi Huang; Christophe Colin; Franck Bassinot; Zhaojie Yu; Quentin Dubois-Dauphin; Arnaud Dapoigny; David J. Wilson; Germain Bayon (Earth and Planetary Science Letters, 2024)

Photosynthetic pretreatment increases membrane-based rejection of boron and arsenic - Weishi Wang; Colin Wilson Root; Henry F. Peel; Maximilian Garza; Nicholas Gidley; Giuliana Romero-Mariscal; Lino Morales-Paredes; Armando Arenazas-Rodríguez; Juana Ticona-Quea; Johan Vanneste; Gary F. Vanzin; Jonathan O. Sharp (Water Research, 2024)

The radiometric environment for Mars limb observations by the Mars Sample Return Earth Return Orbiter - Marek Slipski; Armin Kleinböhl; Daniela Tirsch; Gerhard Kminek; Gregory Jonniaux; Klaus-Dieter Matz; Anni Määttänen; Austin Nicholas; Franck Montmessin; Soren N. Madsen; Matthew Abrahamson; Manuel Sanchez-Gestido; et al. (Advances in Space Research, 2023)

Preface for special issue on the Colour and Stereo Surface Imaging System (CaSSIS) at Mars - Elliot Sefton-Nash; James Wray; Ernst Hauber; Nicolas Thomas; Colin Wilson (Planetary and Space Science, 2023)

Crustal basement terranes under the Taupō Volcanic Zone, New Zealand: Context for hydrothermal and magmatic processes - Nick Mortimer; Bruce L.A. Charlier; Shane M. Rooyakkers; Rose E. Turnbull; Colin J.N. Wilson; Marianne Negrini; Stephen Bannister; Sarah D. Milicich; Isabelle Chambefort; Craig A. Miller; Geoff Kilgour (Journal of Volcanology and Geothermal Research, 2023)

Absence of low-δ18O magmas despite widespread assimilation of altered crust in a large magmatic and hydrothermal province - Shane M. Rooyakkers; Isabelle Chambefort; Kevin Faure; Colin J.N. Wilson; Simon J. Barker; Nick Mortimer; Hannah C. Elms; Juliana Troch; Bruce L.A. Charlier; Graham S. Leonard; David Farsky (Geochimica et Cosmochimica Acta, 2023)

Millimetre‐scale pollen analysis of non‐varved lacustrine sediments from Onepoto maar palaeolake, Auckland, reveals distal vegetation responses and landscape recovery following the ~25.5‐ka Ōruanui supereruption, New Zealand - Stephen B. Piva; Simon J. Barker; Rewi M. Newnham; Andrew B. H. Rees; Colin J. N. Wilson; Lionel Carter; Nels A. Iverson; Benjamin Läuchli; Paul C. Augustinus (Journal of Quaternary Science, 2023)
The ~25.5‐ka Ōruanui supereruption (Taupō volcano, New Zealand) erupted >1100 km 3 of pyroclastic material during the Last Glacial Maximum. The impacts of this event on climate and the New Zealand environment remain unresolved, particularly on ecological timescales. Using sediment cores from Onepoto maar palaeolake, Auckland (~240 km upwind from source), we have analysed pollen assemblages at contiguous 1‐mm intervals, around an intact 3‐cm layer of the Kawakawa‐Ōruanui Tephra to resolve and assess post‐eruption vegetation impacts and landscape recovery. Sediments immediately above the tephra record a decline in the relative abundance of the dominant canopy species of Fuscospora , and concurrent increase in the abundances of grasses, herbs, ferns and shrubs. These changes reflect a brief (

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

An integrated proximal-distal radiocarbon dating approach provides improved age constraints for a key Holocene tephra isochron - Charlotte O. Pizer; Jamie D. Howarth; Kate J. Clark; Colin J.N. Wilson; Stephanie E. Tickle; Jenni L. Hopkins; Jenny A. Dahl (Quaternary Science Reviews, 2023)

Processes and timescales of magmatic rejuvenation and residence prior to post-caldera rhyolitic eruptions: Ōkataina Volcanic Centre, Aotearoa New Zealand - Hannah C. Elms; Simon J. Barker; Daniel J. Morgan; Colin J.N. Wilson; Bruce L.A. Charlier (Journal of Volcanology and Geothermal Research, 2023)

The compositional diversity and temporal evolution of an active andesitic arc stratovolcano: Tongariro, Taupō Volcanic Zone, New Zealand - Leo R. Pure; Colin J. N. Wilson; Bruce L. A. Charlier; John A. Gamble; Dougal B. Townsend; Graham S. Leonard (Contributions to Mineralogy and Petrology, 2023)
New geochemical data, including Sr–Nd–Pb isotopes for whole-rock and groundmass samples, are reported for edifice-forming eruptives at Tongariro volcano, New Zealand, which span its ~ 350 ka to late Holocene history. Tongariro eruptives are medium-K basaltic-andesites to dacites (53.0–66.2 wt% SiO 2 ) that evolved via assimilation-fractional crystallisation (AFC) processes partly or mostly in the uppermost 15 km of the crust. When ordered chronologically using a high-resolution 40 Ar/ 39 Ar-dated eruptive stratigraphy, the compositional data show systematic 10–130 kyr cycles. Mafic replenishment events inferred from MgO values occurred at ~ 230, ~ 151, ~ 88 and ~ 56 ka and in the late Holocene, with high-MgO flank vents erupting at ~ 160, ~ 117, ~ 35 and ~ 17.5 ka. Cycles in Sm/Nd, 87 Sr/ 86 Sr, 143 Nd/ 144 Nd and Pb isotopic ratios, which are decoupled from MgO, K 2 O and Rb/Sr cycles, indicate periods of prolonged crustal residence of magmas from ~ 230 to ~ 100 ka and ~ 95 to ~ 30 ka. AFC modelling shows that intermediate and silicic melt compositions, with r-values between 0.1 and 1, are needed to reproduce Tongariro compositional arrays. AFC models also indicate that ~ 20% of the average Tongariro magma comprises assimilated (meta)sedimentary basement material. Locally, Tongariro and adjacent Ruapehu volcanoes attain their most crust-like 87 Sr/ 86 Sr and 143 Nd/ 144 Nd compositions at ~ 100 and ~ 30 ka, paralleling with zircon model-age crystallisation modes at the rhyolitic Taupō volcano ~ 50 km to the NNE. These coincidences suggest that the timing and tempo of magma assembly processes at all three volcanoes were contemporaneous and may have been tectonically influenced since at least 200 ka.

Correction: Textural and micro-analytical insights into mafic–felsic interactions during the Oruanui eruption, Taupo - Shane M. Rooyakkers; Colin J. N. Wilson; C. Ian Schipper; Simon J. Barker; Aidan S. R. Allan (Contributions to Mineralogy and Petrology, 2023)

Belize Blue Carbon: Establishing a national carbon stock estimate for mangrove ecosystems - Hannah K. Morrissette; Stacy K. Baez; Lisa Beers; Nadia Bood; Ninon D. Martinez; Kevin Novelo; Gilbert Andrews; Luis Balan; C. Scott Beers; Sumeet A. Betancourt; Reynel Blanco; Eeryn Bowden; et al. (Science of The Total Environment, 2023)

Assessing the ecological suitability of the Irish landscape for the Eurasian lynx (Lynx lynx) - Colin Guilfoyle; Ryan Wilson-Parr; Joanne O’Brien (Mammal Research, 2023)

Pre-eruptive rhyolite magma ascent rate is rapid and independent of eruption size: a case study from Ōkataina Volcanic Centre, Aotearoa New Zealand - Hannah C. Elms; Madison L. Myers; Alexander R. L. Nichols; Paul J. Wallace; Colin J. N. Wilson; Simon J. Barker; Bruce L. A. Charlier (Bulletin of Volcanology, 2023)
Volatile measurements in mineral-hosted sealed melt inclusions, and open-ended embayments, have previously been used to study magma ascent dynamics in large rhyolitic eruptions. However, despite occurring more frequently, smaller-volume explosive events remain under-studied. We present magmatic volatile data from quartz-hosted melt inclusions and embayments for eight post-25.4 ka rhyolitic eruptions at Ōkataina Volcanic Centre, Aotearoa New Zealand. Seven originated from within the main caldera, and the other erupted from the associated Ōkareka Structural Embayment. Melt inclusions preserve volatile contents of 2.92–5.82 wt% H 2 O and 13–126 ppm CO 2 , indicating pre-eruptive storage depths of 4.5–7.4 km, with younger eruptions being more shallow. The lack of correlation between H 2 O, CO 2 , inclusion size or distance to the crystal rim suggests magma bodies experienced variable degrees of degassing during magma storage, with some amount of post-entrapment volatile modification prior to and concurrent with final magma ascent. Diffusion modelling of measured H 2 O gradients in melt embayments indicates ascent rates of 0.10–1.67 m.s −1 over time spans of 20–230 min for the intra-caldera events. In contrast, ascent rates for the eruption from the Ōkareka Structural Embayment may be more rapid, at 1.59–4.4 m.s −1 over a time span of 22–34 min. Our findings imply that the final, pre-eruptive magma movement towards the surface could be less than a few hours. Comparisons with published data for caldera-forming explosive events reveal no clear relationships between final ascent rate, eruption size or initial volatile content, implying that other factors besides eruption volume control rhyolite magma ascent.

Beware the foe who feels no pain: Associations between relative formidability and pain sensitivity in three U.S. online studies - Daniel M.T. Fessler; Wilson Merrell; Colin Holbrook; Joshua Ackerman (Evolution and Human Behavior, 2023)

A sulfur and halogen budget for the large magmatic system beneath Taupō volcano - Max S. Sharpe; Simon J. Barker; Shane M. Rooyakkers; Colin J. N. Wilson; Isabelle Chambefort; Michael C. Rowe; C. Ian Schipper; Bruce L. A. Charlier (Contributions to Mineralogy and Petrology, 2022)
The transport and degassing pathways of volatiles through large silicic magmatic systems are central to understanding geothermal fluid compositions, ore deposit genesis, and volcanic eruption dynamics and impacts. Here, we document sulfur (S), chlorine (Cl), and fluorine (F) concentrations in a range of host materials in eruptive deposits from Taupō volcano (New Zealand). Materials analysed are groundmass glass, silicic melt inclusions, and microphenocrystic apatite that equilibrated in shallow melt-dominant magma bodies; silicic melt and apatite inclusions within crystal cores inferred to be sourced from deeper crystal mush; and olivine-hosted basaltic melt inclusions from mafic enclaves that represent the most primitive feedstock magmas. Sulfur and halogen concentrations each follow distinct concentration pathways during magma differentiation in response to changing pressures, temperatures, oxygen fugacities, crystallising mineral phases, the effects of volatile saturation, and the presence of an aqueous fluid phase. Sulfur contents in the basaltic melt inclusions (~ 2000 ppm) are typical for arc-type magmas, but drop to near detection limits by dacitic compositions, reflecting pyrrhotite crystallisation at ~ 60 wt. % SiO 2 during the onset of magnetite crystallisation. In contrast, Cl increases from ~ 500 ppm in basalts to ~ 2500 ppm in dacitic compositions, due to incompatibility in the crystallising phases. Fluorine contents are similar between mafic and silicic compositions (< 1200 ppm) and are primarily controlled by the onset of apatite and/or amphibole crystallisation and then destabilisation. Sulfur and Cl partition strongly into an aqueous fluid and/or vapour phase in the shallow silicic system. Sulfur contents in the rhyolite melts are low, yet the Oruanui supereruption is associated with a major sulfate peak in ice core records in Antarctica and Greenland, implying that excess S was derived from a pre-eruptive gas phase, mafic magma recharge, and/or disintegration of a hydrothermal system. We estimate that the 25.5 ka Oruanui eruption ejected > 130 Tg of S (390 Tg sulfate) and up to ~ 1800 Tg of Cl, with potentially global impacts on climate and stratospheric ozone.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Marine and freshwater regime changes impact a community of migratory Pacific salmonids in decline - Kyle L. Wilson; Colin J. Bailey; Trevor D. Davies; Jonathan W. Moore (Global Change Biology, 2022)
Marine and freshwater ecosystems are increasingly at risk of large and cascading changes from multiple human activities (termed “regime shifts”), which can impact population productivity, resilience, and ecosystem structure. Pacific salmon exhibit persistent and large fluctuations in their population dynamics driven by combinations of intrinsic (e.g., density dependence) and extrinsic factors (e.g., ecosystem changes, species interactions). In recent years, many Pacific salmon have declined due to regime shifts but clear understanding of the processes driving these changes remains elusive. Here, we unpacked the role of density dependence, ecosystem trends, and stochasticity on productivity regimes for a community of five anadromous Pacific salmonids (Steelhead, Coho Salmon, Pink Salmon, Dolly Varden, and Coastal Cutthroat Trout) across a rich 40‐year time‐series. We used a Bayesian multivariate state‐space model to examine whether productivity shifts had similarly occurred across the community and explored marine or freshwater changes associated with those shifts. Overall, we identified three productivity regimes: an early regime (1976–1990), a compensatory regime (1991–2009), and a declining regime (since 2010) where large declines were observed for Steelhead, Dolly Varden, and Cutthroat Trout, intermediate declines in Coho and no change in Pink Salmon. These regime changes were associated with multiple cumulative effects across the salmon life cycle. For example, increased seal densities and ocean competition were associated with lower adult marine survival in Steelhead. Watershed logging also intensified over the past 40 years and was associated with (all else equal) ≥97% declines in freshwater productivity for Steelhead, Cutthroat, and Coho. For Steelhead, marine and freshwater dynamics played approximately equal roles in explaining trends in total productivity. Collectively, these changing environments limited juvenile production and lowered future adult returns. These results reveal how changes in freshwater and marine environments can jointly shape population dynamics among ecological communities, like Pacific salmon, with cascading consequences to their resilience.

A comment on: magma residence and eruption at the Taupō Volcanic Center (Taupō Volcanic Zone, New Zealand)—insights from rhyolite-MELTS geobarometry, diffusion chronometry, and crystal textures, by AS Pamukçu et al., Contrib Mineral Petrol 175:48 (2020) - Colin J. N. Wilson; Simon J. Barker; Bruce L. A. Charlier; Madison L. Myers; Kristian F. Hansen (Contributions to Mineralogy and Petrology, 2021)

Exploring controls of the early and stepped deglaciation on the western margin of the British Irish Ice Sheet - Sara Benetti; Richard C. Chiverrell; Colm Ó Cofaigh; Matt Burke; Alicia Medialdea; David Small; Colin Ballantyne; Mark D. Bateman; S. Louise Callard; Peter Wilson; Derek Fabel; Chris D. Clark; et al. (Journal of Quaternary Science, 2021)
New optically stimulated luminescence dating and Bayesian models integrating all legacy and BRITICE‐CHRONO geochronology facilitated exploration of the controls on the deglaciation of two former sectors of the British–Irish Ice Sheet, the Donegal Bay (DBIS) and Malin Sea ice‐streams (MSIS). Shelf‐edge glaciation occurred ~27 ka, before the global Last Glacial Maximum, and shelf‐wide retreat began 26–26.5 ka at a rate of ~18.7–20.7 m a –1 . MSIS grounding zone wedges and DBIS recessional moraines show episodic retreat punctuated by prolonged still‐stands. By ~23–22 ka the outer shelf (~25 000 km 2 ) was free of grounded ice. After this time, MSIS retreat was faster (~20 m a –1 vs. ~2–6 m a –1 of DBIS). Separation of Irish and Scottish ice sources occurred ~20–19.5 ka, leaving an autonomous Donegal ice dome. Inner Malin shelf deglaciation followed the submarine troughs reaching the Hebridean coast ~19 ka. DBIS retreat formed the extensive complex of moraines in outer Donegal Bay at 20.5–19 ka. DBIS retreated on land by ~17–16 ka. Isolated ice caps in Scotland and Ireland persisted until ~14.5 ka. Early retreat of this marine‐terminating margin is best explained by local ice loading increasing water depths and promoting calving ice losses rather than by changes in global temperatures. Topographical controls governed the differences between the ice‐stream retreat from mid‐shelf to the coast.

Central Asian wild tulip conservation requires a regional approach, especially in the face of climate change - Brett Wilson; Aibek Dolotbakov; Benjamin J. Burgess; Colin Clubbe; Georgy Lazkov; Kaiyrkul Shalpykov; Myskalai Ganybaeva; Ormon Sultangaziev; Samuel F. Brockington (Biodiversity and Conservation, 2021)
Tulips ( Tulipa spp.) are one of the most widely appreciated plants worldwide, nevertheless species taxonomy and biogeography are often poorly understood. Most wild tulips inhabit the mountains of Central Asia, a recognised biodiversity hotspot, and a centre of tulip diversity. Despite the presence of several country-level endemic Tulipa species, most taxa span the borders of several nations. With no globally Red Listed tulip taxa from this region national level conservation assessments are an important resource. Nonetheless, threats posed to tulips are still inadequately understood, especially climate change, and given the trans-national nature of most species, distributional information is restricted and often misleading. Here we collate 330 species records from the Global Biodiversity Information Facility with 85 newly collected records, to undertake species distribution modelling (MaxEnt) for ten native Central Asian species. This work showed that regional level models provide a much more comprehensive understanding of species’ extinction risks, proportions of habitat in different countries, and limitations in protected area coverage. Furthermore, our climate modelling, the first of its kind for tulips, suggests that climate change will have a significant negative impact on the range size of all species; including those that are currently widespread. We therefore add climate change to the list of threats affecting tulip populations in Central Asia, which already includes livestock overgrazing, urbanisation, wild collection, and mining. Overall, our work shows that although national information is important, a regional approach is crucial not just for tulip conservation efforts, but likely for Central Asian plant conservation in general.

The ontogeny of Na+ uptake in larval rainbow trout reared in waters of different Na+ content - Emily J. Gallagher; Till S. Harter; Jonathan M. Wilson; Colin J. Brauner (Journal of Comparative Physiology B, 2021)

Home testing for COVID-19: lessons from direct to consumer genetics - Theodore E. Wilson; Colin Halverson (Journal of Community Genetics, 2020)

Effects of 21st‐century climate, land use, and disturbances on ecosystem carbon balance in California - Benjamin M. Sleeter; David C. Marvin; D. Richard Cameron; Paul C. Selmants; A.LeRoy Westerling; Jason Kreitler; Colin J. Daniel; Jinxun Liu; Tamara S. Wilson (Global Change Biology, 2019)
Terrestrial ecosystems are an important sink for atmospheric carbon dioxide (CO 2 ), sequestering ~30% of annual anthropogenic emissions and slowing the rise of atmospheric CO 2 . However, the future direction and magnitude of the land sink is highly uncertain. We examined how historical and projected changes in climate, land use, and ecosystem disturbances affect the carbon balance of terrestrial ecosystems in California over the period 2001–2100. We modeled 32 unique scenarios, spanning 4 land use and 2 radiative forcing scenarios as simulated by four global climate models. Between 2001 and 2015, carbon storage in California's terrestrial ecosystems declined by −188.4 Tg C, with a mean annual flux ranging from a source of −89.8 Tg C/year to a sink of 60.1 Tg C/year. The large variability in the magnitude of the state's carbon source/sink was primarily attributable to interannual variability in weather and climate, which affected the rate of carbon uptake in vegetation and the rate of ecosystem respiration. Under nearly all future scenarios, carbon storage in terrestrial ecosystems was projected to decline, with an average loss of −9.4% (−432.3 Tg C) by the year 2100 from current stocks. However, uncertainty in the magnitude of carbon loss was high, with individual scenario projections ranging from −916.2 to 121.2 Tg C and was largely driven by differences in future climate conditions projected by climate models. Moving from a high to a low radiative forcing scenario reduced net ecosystem carbon loss by 21% and when combined with reductions in land‐use change (i.e., moving from a high to a low land‐use scenario), net carbon losses were reduced by 55% on average. However, reconciling large uncertainties associated with the effect of increasing atmospheric CO 2 is needed to better constrain models used to establish baseline conditions from which ecosystem‐based climate mitigation strategies can be evaluated.

Insect population trends and the IUCN Red List process - Richard Fox; Colin A. Harrower; James R. Bell; Chris R. Shortall; Ian Middlebrook; Robert J. Wilson (Journal of Insect Conservation, 2019)

Deglaciation chronology of the Donegal Ice Centre, north‐west Ireland - Peter Wilson; Colin K. Ballantyne; Sara Benetti; David Small; Derek Fabel; Chris D. Clark (Journal of Quaternary Science, 2019)
During the Last Glacial Maximum, Donegal in north‐west Ireland functioned as an independent centre of ice dispersal that separated and fed into the Donegal Bay Ice Lobe (sourced in the Irish Midlands) to the south and the Hebrides/Malin Sea Ice Stream to the north. We report geochronological data that demonstrate marked contrasts in the timing and rate of deglaciation in northern and southern Donegal. In northern Donegal, which occupied an inter‐ice‐stream/lobe location, decoupling from the Hebrides/Malin Sea Ice Stream resulted in formation of a marine embayment along the north coast by ∼22–21 ka, and subsequent slow (∼4 ± 1 m a −1 ) climatically driven inland retreat of the ice margin to mountain source areas by ∼17 ka. By contrast, in southern Donegal, which lay near the axis of the Donegal Bay Ice Lobe, deglaciation was delayed until ∼18 ka following readvance of ice to a moraine in outer Donegal Bay. The ice margin subsequently underwent net retreat, apparently uninterrupted by readvances, at a net rate of ∼ 18 ± 6 m a −1 . A mean terrestrial cosmogenic nuclide age of ∼15.0 ka obtained for samples from the foothills of the Blue Stack Mountains in south‐east Donegal indicates that ice persisted in valley heads and cirques at the beginning of the Lateglacial Interstadial, suggesting that these and nearby mountains supported the last remnants of the Irish Ice Sheet before complete deglaciation of Ireland, and that almost all the shrinkage of the ice sheet in this sector occurred under stadial conditions before the onset of interstadial warming at ∼14.7 ka.

Zn2+-binding in the glutamate-rich region of the intrinsically disordered protein prothymosin-alpha - Sriramya Garapati; William Monteith; Chris Wilson; Anastasiia Kostenko; John M. Kenney; Allison S. Danell; Colin S. Burns (JBIC Journal of Biological Inorganic Chemistry, 2018)

Improving biocontrol of black vine weevil (Otiorhynchus sulcatus) with entomopathogenic fungi in growing media by incorporating spent mushroom compost - Ralph Noble; Andreja Dobrovin-Pennington; Jean Fitzgerald; Katie Dew; Craig Wilson; Kyle Ross; Colin Perkins (BioControl, 2018)

Chronic impacts of invasive herbivores on a foundational forest species: a whole‐tree perspective - Claire M. Wilson; Robert N. Schaeffer; Mauri L. Hickin; Chad M. Rigsby; Amanda F. Sommi; Carol S. Thornber; Colin M. Orians; Evan L. Preisser (Ecology, 2018)
Forests make up a large portion of terrestrial plant biomass, and the long‐lived woody plants that dominate them possess an array of traits that deter consumption by forest pests. Although often extremely effective against native consumers, invasive species that avoid or overcome these defenses can wreak havoc on trees and surrounding ecosystems. This is especially true when multiple invasive species co‐occur, since interactions between invasive herbivores may yield non‐additive effects on the host. While the threat posed by invasive forest pests is well known, long‐term field experiments are necessary to explore these consumer‐host interactions at appropriate spatial and temporal scales. Moreover, it is important to measure multiple variables to get a “whole‐plant” picture of their combined impact. We report the results of a 4‐yr field experiment addressing the individual and combined impacts of two invasive herbivores, the hemlock woolly adelgid ( Adelges tsugae ) and elongate hemlock scale ( Fiorinia externa ), on native eastern hemlock ( Tsuga canadensis ) in southern New England. In 2011, we planted 200 hemlock saplings into a temperate forest understory and experimentally manipulated the presence/absence of both herbivore species; in 2015, we harvested the 88 remaining saplings and assessed plant physiology, growth, and resource allocation. Adelgids strongly affected hemlock growth: infested saplings had lower above/belowground biomass ratios, more needle loss, and produced fewer new needles than control saplings. Hemlock scale did not alter plant biomass allocation or growth, and its co‐occurrence did not alter the impact of adelgid. While both adelgid and scale impacted the concentrations of primary metabolites, adelgid effects were more pronounced. Adelgid feeding simultaneously increased free amino acids local to feeding sites and a ~30% reduction in starch. The cumulative impact of adelgid‐induced needle loss, manipulation of nitrogen pools, and the loss of stored resources likely accelerates host decline through disruption of homeostatic source‐sink dynamics occurring at the whole‐plant level. Our research stresses the importance of considering long‐term impacts to predict how plants will cope with contemporary pressures experienced in disturbed forests.

Correction to: Contrasting perspectives on the Lava Creek Tuff eruption, Yellowstone, from new U–Pb and 40Ar/39Ar age determinations - Colin J. N. Wilson; Mark E. Stelten; Jacob B. Lowenstern (Bulletin of Volcanology, 2018)

Contrasting perspectives on the Lava Creek Tuff eruption, Yellowstone, from new U–Pb and 40Ar/39Ar age determinations - Colin J. N. Wilson; Mark E. Stelten; Jacob B. Lowenstern (Bulletin of Volcanology, 2018)

Textural and micro-analytical insights into mafic–felsic interactions during the Oruanui eruption, Taupo - Shane M. Rooyakkers; Colin J. N. Wilson; C. Ian Schipper; Simon J. Barker; Aidan S. R. Allan (Contributions to Mineralogy and Petrology, 2018)

Evacuation of multiple magma bodies and the onset of caldera collapse in a supereruption, captured in glass and mineral compositions - Elliot J. Swallow; Colin J. N. Wilson; Madison L. Myers; Paul J. Wallace; Katie S. Collins; Euan G. C. Smith (Contributions to Mineralogy and Petrology, 2018)

A cascade of magmatic events during the assembly and eruption of a super-sized magma body - Aidan. S. R. Allan; Simon J. Barker; Marc-Alban Millet; Daniel J. Morgan; Shane M. Rooyakkers; C. Ian Schipper; Colin J. N. Wilson (Contributions to Mineralogy and Petrology, 2017)

Multi-criteria correlation of tephra deposits to source centres applied in the Auckland Volcanic Field, New Zealand - Jenni L. Hopkins; Colin J. N. Wilson; Marc-Alban Millet; Graham S. Leonard; Christian Timm; Lucy E. McGee; Ian E. M. Smith; Euan G. C. Smith (Bulletin of Volcanology, 2017)

Eruptive and environmental processes recorded by diatoms in volcanically dispersed lake sediments from the Taupo Volcanic Zone, New Zealand - Margaret A. Harper; Shirley A. Pledger; Euan G. C. Smith; Alexa R. Van Eaton; Colin J. N. Wilson (Journal of Paleolimnology, 2015)

Fine-scale temporal recovery, reconstruction and evolution of a post-supereruption magmatic system - Simon J. Barker; Colin J. N. Wilson; Aidan S. R. Allan; C. Ian Schipper (Contributions to Mineralogy and Petrology, 2015)

Bubble development in explosive silicic eruptions: insights from pyroclast vesicularity textures from Raoul volcano (Kermadec arc) - Melissa D. Rotella; Colin J. N. Wilson; Simon J. Barker; Katharine V. Cashman; Bruce F. Houghton; Ian C. Wright (Bulletin of Volcanology, 2014)

Timescales of mixing and mobilisation in the Bishop Tuff magma body: perspectives from diffusion chronometry - Katy J. Chamberlain; Daniel J. Morgan; Colin J. N. Wilson (Contributions to Mineralogy and Petrology, 2014)

Temporal evolution and compositional signatures of two supervolcanic systems recorded in zircons from Mangakino volcanic centre, New Zealand - George F. Cooper; Colin J. N. Wilson; Bruce L. A. Charlier; Joseph L. Wooden; Trevor R. Ireland (Contributions to Mineralogy and Petrology, 2014)

Corrosion of metal roof materials related to volcanic ash interactions - Christopher Oze; Jim Cole; Allan Scott; Thomas Wilson; Grant Wilson; Sally Gaw; Samuel Hampton; Colin Doyle; Zhengwei Li (Natural Hazards, 2014)

Lateglacial rock slope failures in north‐west Ireland: age, causes and implications - COLIN K. BALLANTYNE; PETER WILSON; CHRISTOPH SCHNABEL; SHENG XU (Journal of Quaternary Science, 2013)
Nine postglacial quartzite rock slope failures (RSFs) in north‐west Ireland were dated using cosmogenic 10 Be. Weighted mean RSF ages range from 17.7 ± 0.9 to 12.5 ± 0.7 ka or 16.6 ± 0.7 to 11.7 ± 0.5 ka, depending on assumed 10 Be production rate. All dated RSFs occurred within ∼5000 years following ice‐sheet deglaciation at ∼17.4ka (∼16.3 ka) and all but two occurred within 2000 years after deglaciation. The timing of RSFs rules out glacial ‘debuttressing’, permafrost degradation and enhanced deglacial cleft‐water pressures as triggers of failure in most cases. We infer that paraglacial stress release and associated fracture propagation were critical in reducing rock masses to critical stability, although earthquakes caused by Lateglacial glacio‐isostatic rebound and/or release of stored tectonic stresses may have triggered failure in some or all cases. In conjunction with data from related studies, our results imply that most undated RSFs outside the limit of Younger Dryas glaciation in the British Isles are of Lateglacial age, and that numerous Lateglacial RSFs occurred inside these limits, with subsequent removal of debris by glaciers. They support the view that paraglacial RSF activity in tectonically stable intraplate terrains was concentrated within a few millennia following deglaciation.

From mush to eruption in centuries: assembly of the super-sized Oruanui magma body - Aidan S. R. Allan; Daniel J. Morgan; Colin J. N. Wilson; Marc-Alban Millet (Contributions to Mineralogy and Petrology, 2013)

New methods and technologies for regional-scale abundance estimation of land-breeding marine animals: application to Adélie penguin populations in East Antarctica - Colin Southwell; John McKinlay; Matt Low; David Wilson; Kym Newbery; Jan L. Lieser; Louise Emmerson (Polar Biology, 2013)

Complex social structure of southern flying squirrels is related to spatial proximity but not kinship - Colin J. Garroway; Jeff Bowman; Paul J. Wilson (Behavioral Ecology and Sociobiology, 2013)

Differential localisation of BPIFA1 (SPLUNC1) and BPIFB1 (LPLUNC1) in the nasal and oral cavities of mice - Maslinda Musa; Kirsty Wilson; Le Sun; Apoorva Mulay; Lynne Bingle; Helen M. Marriott; Elizabeth E. LeClair; Colin D. Bingle (Cell and Tissue Research, 2012)

BPIFB1 (LPLUNC1) is upregulated in cystic fibrosis lung disease - Lynne Bingle; Kirsty Wilson; Maslinda Musa; Bianca Araujo; Doris Rassl; William A. Wallace; Elizabeth E. LeClair; Thais Mauad; Zhe Zhou; Marcus A. Mall; Colin D. Bingle (Histochemistry and Cell Biology, 2012)

Growth of volcanic ash aggregates in the presence of liquid water and ice: an experimental approach - Alexa R. Van Eaton; James D. Muirhead; Colin J. N. Wilson; Corrado Cimarelli (Bulletin of Volcanology, 2012)

A comment on: ‘TitaniQ under pressure: the effect of pressure and temperature on the solubility of Ti in quartz’, by Jay B. Thomas, E. Bruce Watson, Frank S. Spear, Philip T. Shemella, Saroj K. Nayak and Antonio Lanzirotti - Colin J. N. Wilson; Terry M. Seward; Aidan S. R. Allan; Bruce L. A. Charlier; Léa Bello (Contributions to Mineralogy and Petrology, 2012)

Contrasting pyroclast density spectra from subaerial and submarine silicic eruptions in the Kermadec arc: implications for eruption processes and dredge sampling - Simon J. Barker; Melissa D. Rotella; Colin J. N. Wilson; Ian C. Wright; Richard J. Wysoczanski (Bulletin of Volcanology, 2012)

Neuromelanin Activates Microglia and Induces Degeneration of Dopaminergic Neurons: Implications for Progression of Parkinson’s Disease - Wei Zhang; Kester Phillips; Albert R. Wielgus; Jie Liu; Alberto Albertini; Fabio A. Zucca; Rudolph Faust; Steven Y. Qian; David S. Miller; Colin F. Chignell; Belinda Wilson; Vernice Jackson-Lewis; et al. (Neurotoxicity Research, 2011)

A virgin flight across the Tasman Sea? Satellite tracking of post-fledging movement in the Australasian Gannet Morus serrator - Stefanie M. H. Ismar; Colin Hunter; Kevin Lay; Tamsin Ward-Smith; Peter R. Wilson; Mark E. Hauber (Journal of Ornithology, 2010)

Human LPLUNC1 is a secreted product of goblet cells and minor glands of the respiratory and upper aerodigestive tracts - Colin D. Bingle; Kirsty Wilson; Hayley Lunn; Frances A. Barnes; Alec S. High; William A. Wallace; Doris Rassl; Michael A. Campos; Manuel Ribeiro; Lynne Bingle (Histochemistry and Cell Biology, 2010)

Aquaporin-1 in blood vessels of rat circumventricular organs - Alan J. Wilson; Colin J. Carati; Bren J. Gannon; Rainer Haberberger; Tim K. Chataway (Cell and Tissue Research, 2010)

Climate change induced hybridization in flying squirrels - COLIN J. GARROWAY; JEFF BOWMAN; TARA J. CASCADEN; GILLIAN L. HOLLOWAY; CAROLYN G. MAHAN; JAY R. MALCOLM; MICHAEL A. STEELE; GREGORY TURNER; PAUL J. WILSON (Global Change Biology, 2010)
There is now unequivocal evidence for global climate change; however, its potential impacts on evolutionary processes remain unclear. Many species have responded to contemporary climate change through shifts in their geographic range. This could lead to increased sympatry between recently diverged species; likely increasing the potential for hybridization. Recently, following a series of warm winters, southern flying squirrels ( Glaucomys volans ) in Ontario, Canada rapidly expanded their northern range limit resulting in increased sympatry with the closely related northern flying squirrel ( Glaucomys sabrinus ). This provided the opportunity to test the prediction that contemporary climate change can act as a catalyst creating conditions for the formation of hybrid zones. Following extensive sampling and molecular analyses (nuclear and mitochondrial DNA), we identified the occurrence of hybridization between sympatric G. sabrinus and G. volans . There was evidence of backcrossing but not of extensive introgession, consistent with the hypothesis of recent rather than historic hybridization. To our knowledge, this is the first report of hybrid zone formation following a range expansion induced by contemporary climate change. This is also the first report of hybridization between North American flying squirrel species.

Does the preferential microbial colonisation of ferromagnesian minerals affect mineral weathering in soil? - Michael J. Wilson; Giacomo Certini; Colin D. Campbell; Ian C. Anderson; Stephen Hillier (The Science of Nature, 2008)

Does Breeding Site Fidelity Drive Phenotypic and Genetic Sub-Structuring of a Population of Arctic Charr? - Colin E. Adams; Deborah J. Hamilton; Ian Mccarthy; Alastair J. Wilson; Alan Grant; Gavin Alexander; Susan Waldron; Sigurdur S. Snorasson; Moira M. Ferguson; Skuli Skúlason (Evolutionary Ecology, 2006)

Mixing and differentiation in the Oruanui rhyolitic magma, Taupo, New Zealand: evidence from volatiles and trace elements in melt inclusions - Yang Liu; Alfred T. Anderson; Colin J. N. Wilson; Andrew M. Davis; Ian M. Steele (Contributions to Mineralogy and Petrology, 2006)

Y chromosome haplogroups of elite Ethiopian endurance runners - Colin N. Moran; Robert A. Scott; Susan M. Adams; Samantha J. Warrington; Mark A. Jobling; Richard H. Wilson; William H. Goodwin; Evelina Georgiades; Bezabhe Wolde; Yannis P. Pitsiladis (Human Genetics, 2004)

Palaeotemperature determinations for the 1.8-ka Taupo ignimbrite, New Zealand, and implications for the emplacement history of a high-velocity pyroclastic flow - Elizabeth McClelland; Colin J. N. Wilson; Leon Bardot (Bulletin of Volcanology, 2004)

Blood-respiratory and acid?base changes during extended diving in the bimodally respiring freshwater turtle Rheodytes leukops - Matthew A. Gordos; Craig E. Franklin; Colin J. Limpus; Gary Wilson (Journal of Comparative Physiology B, 2004)

Sequence, evolution and ligand binding properties of mammalian Duffy antigen/receptor for chemokines - Christophe Tournamille; Antoine Blancher; Caroline Le Van Kim; Pierre Gane; Pol Andr Apoil; Wilson Nakamoto; Jean Pierre Cartron; Yves Colin (Immunogenetics, 2004)